1999
DOI: 10.1139/g99-008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of duplicate genes in soybean

Abstract: Appressed pubescence genes in soybean cause hairs on the upper surface of leaves to lie flat, while pubescence remains erect elsewhere on the plant. For decades this trait was believed to be controlled in soybean by duplicated single genes, Pa1 and Pa2. However, reports in the literature conflicted as to which phenotype was dominant or recessive. Two populations were developed, each approximately 100 individuals, and each segregating for one of the appressed pubescence genes. A combination of SSRs (simple sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
1
26
2
Order By: Relevance
“…Soybean possesses a complicated genome in which homeologous duplicated regions are scattered across different linkage groups (Shoemaker et al 1996;Lee et al 1999). Mapping studies with RFLP markers have revealed that LGs I and O share such homeologous duplicated regions, which are anchored by seven RFLP Figure 3.-PCR amplification of the GmphyA2 fragments specific to homozygous plants for the E4 or e4 alleles and segregations of PCR-amplified fragments for GmphyA1 and GmphyA2 in mapping populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean possesses a complicated genome in which homeologous duplicated regions are scattered across different linkage groups (Shoemaker et al 1996;Lee et al 1999). Mapping studies with RFLP markers have revealed that LGs I and O share such homeologous duplicated regions, which are anchored by seven RFLP Figure 3.-PCR amplification of the GmphyA2 fragments specific to homozygous plants for the E4 or e4 alleles and segregations of PCR-amplified fragments for GmphyA1 and GmphyA2 in mapping populations.…”
Section: Resultsmentioning
confidence: 99%
“…The doubling of the base chromosome number in soybean (x ¼ 20) suggested the hypothesis that soybean is a diplodized tetraploid species (Lackey 1980;Hymowitz 2004). This hypothesis was confirmed by extensive studies utilizing DNA hybridization and genetic mapping with restriction fragment length polymorphism (RFLP) markers, which demonstrated that soybean possesses a high level of duplicate sequences, and furthermore, homeologous duplicated regions anchored by RFLP markers are scattered across different linkage groups in a complex manner (Zhu et al 1994;Shoemaker et al 1996;Lohnes et al 1997;Lee et al 1999). On the basis of the genetic distances estimated by synonymous substitution measurements for the pairs of duplicated transcripts from the EST collections of soybean and M. truncatula, Schlueter et al (2004) estimated that soybean probably underwent two major genome duplication events: one which took place 15 million years ago (MYA) and another 44 MYA.…”
mentioning
confidence: 95%
“…It is unlikely that legumes are an exception to this. Soybean, for example, has long been known to be an ancient polyploid with putative homoeologous chromosomal regions readily identified by genetic mapping (Shoemaker et al, 1996;Lee et al, 1999Lee et al, , 2001 and by characterization of homoeologous bacterial artificial chromosome (BAC) clones (Foster-Hartnett et al, 2002;Yan et al, 2003). And recently, segmental duplications within the soybean genome were visualized by fluorescence in situ hybridization of BACs (Pagel et al, 2004).…”
Section: Duplications That Shape the Legume Genomesmentioning
confidence: 99%
“…In addition, fluorescence in situ hybridization analyses using bacterial artificial chromosomes (BACs) have allowed the identification of segmental duplications and chromosome-level homeology within the soybean genome (Pagel et al, 2004;Walling et al, 2006). Genetic mapping has confirmed many duplicated regions of the soybean genome (Shoemaker et al, 1996;Lee et al, 1999Lee et al, , 2001Cai et al, 2008b), and high levels of microsynteny were observed within homeologous BACs screened by RFLP probes (Yan et al, 2003(Yan et al, , 2004.…”
mentioning
confidence: 99%